Modelling of a PLC based interlock logic mudule in process control environment by using frame-based rules-driven approach ... [et al.] / [microfilm] - 366902 Foong, Lee Yi (Skudai : Universiti Teknologi Malaysia, 1998)
Project Paper (Bachelor of Electrical Engineering) - Universiti Teknologi Malaysia, 1998